A BIOTECHNOLOGY FOR PRODUCTION OF BIOETHANOL FROM STEMS SWEET SORGHUM (Sorghum saccharatum (L.)Pers.) - Sarsenbayev, B.A.; Kirshibayev, E.A.; Kamunur, M.; Baiseitova, G.A.; Sarybayeva, E.A.; Nokerbekova , N.K. (Eurasian Journal of Applied Biotechnology, 2013)
Global climate change, which is accompanied by an increase in temperature, a decrease of water resources, reduction in rainfall patterns, expanding acreage areas of drought and desertification is one of the key environmental issues of the earth. This is a good reason to search for and identify the most drought-resistant, heat-resistant and at the same time highly productive crops to meet the needs of the food industry, feed industry and alternative renewable energy in new emerging environments. Sorghum fits the bill. The use of sorghum plant as a substitute for sugar in the food industry and a source of renewable energy is not considered. The paper present the results of a study of the biological productivity of the most common varieties of sugar sorghum in soil and climatic conditions of the south-east of Kazakhstan. It is shown that the investigated varieties of sorghum are all the stages of growth, development and ripen before the first frost. Produced evidence that reflect the biological productivity of the studied varieties. Cultivars differed on a number of biometric parameters. The content of soluble sugars and the dynamics of their accumulation in specific organs by refractometry. The regularities of distribution of soluble sugars by the authorities and the interstices.The experimental data to identify the optimal conditions of fermentation for ethanol from sweet sorghum syrup. It is concluded that sorghum can be included in the list of promising crop for cultivation in arid and variable soil and climatic conditions of the south-east of Kazakhstan as an alternative, renewable and environmentally promising source of energy.